Islamic Spirituality and Subjective Well-Being Among University Students: The Mediating Role of Contentment with Life - Annatagia, Libbie; Rusdi, Ahmad (International Journal of Islamic Educational Psychology, 2026)
University students often face various academic and non-academic challenges that may affect their well-being. This study examines the role of Islamic spirituality in predicting subjective well-being among university students, with a focus on the mediating effect of life satisfaction. A total of 191 university students participated in this study and completed measures of Islamic spirituality, life contentment and satisfaction, positive and negative affect. Data were analyzed using SEM–path. The results showed that Islamic spirituality significantly predicted life contentment (β = 0.45), life satisfaction (β = 0.29), positive affect (β = 0.53), and negative affect (β = −0.27). Contentment with life significantly predicted satisfaction with life (β = 0.53), but did not predict positive affect (β = 0.01) or negative affect (β = −0.19). The indirect effect of Islamic spirituality on satisfaction with life through contentment with life was significant (β = 0.24). In contrast, the indirect effects on positive affect (β = 0.00) and negative affect (β = −0.09) were not significant. These findings indicate that contentment with life functions as a mediator only for the cognitive component of subjective well-being, while affective components are influenced primarily through direct pathways. The novelty of this study lies in positioning contentment as a distinct virtue-based construct that explains how spirituality contributes to university students’ well-being. In this regard, university-based support systems, including counseling services, could integrate spirituality and contentment approaches to more effectively promote students’ well-being.